The association of the prothrombin G20210A single-nucleotide polymorphism and the risk of preeclampsia: Systematic review and meta-analysis. (October 2020) - Ahmed, Nadir A.; Hamdan, Hamdan Z.; Kamis, Ammar H.; Adam, Ishag
Abstract: Objective: We conducted this systematic review and meta-analysis to assess the association between the risk of preeclampsia and the prothrombin G20210A single-nucleotide polymorphism. Study design: We followed the "Preferred Reporting Items for Systematic Reviews and Meta-Analyses" guidelines. Relevant published studies were searched in the data base. The retrieved studies were assessed for quality by using the Modified Newcastle-Ottawa Scale for quality assessment. OpenMeta Analyst software was used for the statistics. Results: Twenty-eight case–control studies enrolling 3821 cases and 4808 controls were included in this systematic review and meta-analysis. We found a significantly increased preeclampsia risk associated with the G20210A polymorphism in three models: allele contrast (A vs. G), OR 2.183, 95 % CI 1.665–2.862; heterozygote (AG vs. GG), OR 2.233, 95 % CI 1.690–2.95; and the dominant model (AA + AG vs. GG) OR 2.240, 95 % CI 1.700–2.950. However, the association was not observed in the homozygote (AA vs. GG) OR 1.310, 95 % CI = 0.632–2.713 r recessive model (AA vs. AG + GG), OR 1.315, 95 % CI = 0.642–2.695. Conclusions: In this meta-analysis, the prothrombin G20210A single-nucleotide polymorphism was associated with an increased risk of preeclampsia.